ApoSOD1 lacking dismutase activity neuroprotects motor neurons exposed to beta-methylamino-L-alanine through the Ca(2+)/Akt/ERK1/2 prosurvival pathway - Petrozziello, Tiziana (Cell Death Differ, 2017)
Amyotrophic lateral sclerosis (ALS) is a severe human adult-onset neurodegenerative disease affecting lower and upper motor neurons. In >20% of cases, the familial form of ALS is caused by mutations in the gene encoding Cu,Zn-superoxide dismutase (SOD1). Interestingly, administration of wild-type SOD1 to SOD1(G93A) transgenic rats ameliorates motor symptoms through an unknown mechanism. Here we investigated whether the neuroprotective effects of SOD1 are due to the Ca(2+)-dependent activation of such prosurvival signaling pathway and not to its catalytic activity. To this aim, we also examined the mechanism of neuroprotective action of ApoSOD1, the metal-depleted state of SOD1 that lacks dismutase activity, in differentiated motor neuron-like NSC-34 cells and in primary motor neurons exposed to the cycad neurotoxin beta-methylamino-L-alanine (L-BMAA). Preincubation of ApoSOD1 and SOD1, but not of human recombinant SOD1(G93A), prevented cell death in motor neurons exposed to L-BMAA. Moreover, ApoSOD1 elicited ERK1/2 and Akt phosphorylation in motor neurons through an early increase of intracellular Ca(2+) concentration ([Ca(2+)](i)). Accordingly, inhibition of ERK1/2 by siMEK1 and PD98059 counteracted ApoSOD1- and SOD1-induced neuroprotection. Similarly, transfection of the dominant-negative form of Akt in NSC-34 motor neurons and treatment with the selective PI3K inhibitor LY294002 prevented ApoSOD1- and SOD1-mediated neuroprotective effects in L-BMAA-treated motor neurons. Furthermore, ApoSOD1 and SOD1 prevented the expression of the two markers of L-BMAA-induced ER stress GRP78 and caspase-12. Collectively, our data indicate that ApoSOD1, which is devoid of any catalytic dismutase activity, exerts a neuroprotective effect through an early activation of Ca(2+)/Akt/ERK1/2 pro-survival pathway that, in turn, prevents ER stress in a neurotoxic model of ALS.